2013
DOI: 10.3201/eid1910.130441
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus gattiiInfections in Multiple States Outside the US Pacific Northwest

Abstract: Clonal VGII subtypes (outbreak strains) of Cryptococcus gattii have caused an outbreak in the US Pacific Northwest since 2004. Outbreak-associated infections occur equally in male and female patients (median age 56 years) and usually cause pulmonary disease in persons with underlying medical conditions. Since 2009, a total of 25 C. gattii infections, 23 (92%) caused by non–outbreak strain C. gattii, have been reported from 8 non–Pacific Northwest states. Sixteen (64%) patients were previously healthy, and 21 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 31 publications
4
70
3
Order By: Relevance
“…Single cases of infection have also been reported in the United States, including New England (85,243,247), New Mexico (272), and Florida (253); Europe (91,95,106,245); Asia, including Japan and Singapore (227,246,249); and South America (223,256). Most recently, Harris et al reported 25 cases, inclusive of previously described patients (247,253) diagnosed between 2009 and 2012, from Montana, Alabama, California, Hawaii, and Michigan; none of these patients had traveled to areas of C. gattii endemicity (251). In Australia, despite heightened awareness, no increase in the number cases has been observed (most large institutions care for 2 to 3 patients annually).…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Single cases of infection have also been reported in the United States, including New England (85,243,247), New Mexico (272), and Florida (253); Europe (91,95,106,245); Asia, including Japan and Singapore (227,246,249); and South America (223,256). Most recently, Harris et al reported 25 cases, inclusive of previously described patients (247,253) diagnosed between 2009 and 2012, from Montana, Alabama, California, Hawaii, and Michigan; none of these patients had traveled to areas of C. gattii endemicity (251). In Australia, despite heightened awareness, no increase in the number cases has been observed (most large institutions care for 2 to 3 patients annually).…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 99%
“…VGII infections also occur but are, to date, geographically restricted to the Arnhemland region of the Northern Territory and the southwest of Western Australia (113,117). In contrast, clonal VGII subtypes (referred to as outbreak strains) of C. gattii caused case clusters in British Columbia (subtypes VGIIa and VGIIb) and in the Pacific Northwest (subtypes VGIIa, VGIIb, and VGIIc) (38,132,198,251); subtype VGIIc is a novel subtype not found outside the United States (68). Theories on how these VGII subtypes may have arisen in North America are discussed above (see Epidemiology, Origin, and Evolution, above).…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Posterior fossa mass lesions are rarely diagnosed as Cryptococcoma; hence reports on cerebellar cryptococcoma are limited. In the late stages, it may mimic brain abscess (Li et al, 2010;Harris et al, 2013).…”
Section: Discussionmentioning
confidence: 99%